Human Resource Development: Practices and Technical Framework: Exploring the linkages between HRD mechanisms and organizational efficiency (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Human resources are an organization's greatest assets because without them, everyday business functions such as managing cash flow, making business transactions, communicating through all forms of media, and dealing with customers could not be completed. Human resources and the potential they possess are key drivers for an organization’s success. With globalization and technological advances, today's organizations are continuously changing. Thus, organizational change impacts not only the business but also its employees. In order to maximize organizational effectiveness, human potentials, individuals' capabilities, time, and talents must be managed and developed. Hence, the practice of human resource management (HRM) and human resource development (HRD) works to ensure that employees are able to meet the organization's goals. Keeping the significance of Human Resources in an organization in mind, the present study has been undertaken. The study explores the linkages in human resource development mechanisms generally applied in the organizations and HRD climate variables resulting from it, affecting the development of the employees of the organization and their impact on organizational efficiency and effectiveness. The researches undertaken in the past clearly indicate that there exists a relationship among the HRD mechanisms, HRD climate variables and HRD outcome variables. The efforts have been made to explore these relationships.This paper makes an effort and described that it is the responsibility of the HRD strategists to have a farsighted vision in framing, formulating, and implementing such strategies which could exploit the opportunities available in present scenario to beat the competition. Human Resource Development being one of the most integral parts of Human Resource Management explains the need that the workforceemployees should be developed in such a manner that they prove an asset to the organization. The most important factors contributing to the HRD seems to be a general indifference on the part of employees to their own development through making efforts to recognize their strengths and weaknesses, employees taking training more seriously, top management‘s belief about the importance of human resources, general helpful nature of employees, fairly objective performance appraisals and promotion decisions and tolerance for mistakes.